Asia and Space Tourism. Issue 3 (2nd September 2018) - Lele, Ajey
ABSTRACT: At present, the Asian continent is gaining significant importance in global affairs. The twenty-first century is sometimes described as the "Asian century." As the largest and most populous continent in the world with progressive economics, the Asian continent is emerging as a business center of the world. This offers commercial opportunities in various sectors, including outer space. Further, Asia is emerging as a key hub for science and innovation. In this context, the present state and future prospects of space tourism in Asia are assessed.